PARENTAL INFLUENCE ON CREATIVITY DEVELOPMENT AND VOCATIONAL INTEREST OF CHILDREN IN EKITI STATE NIGERIA - Ojo Oke, Jonathan; Musta'amal, Aede Hatib; Olarewaju Fatokun, Jonathan (Journal of Techno-Social, 2014)
Creativity is a natural endowment which can easily be displayed by children athome. Children are often seen playing with objects and drawings because of their natural quest and inward disposition to explore and come out with creative ideas or products. It is therefore imperative for parents to encourage and develop children at home to achieve this to greater heights. The aim of this study, therefore was to determine the influence of parents in development andvocational interest of children in Ekiti State, Nigeria. The study was carried outusing 400 Junior Secondary School students of age eleven to thirteen as samples. Specifically, the study sought to identify the types of creative activity the students normally engage in; their vocational interests and the influence their parents had in their creativity development and vocational interest. A Child-Creative Inventory Form (CCIF) was used as an instrument for quantitative data collection. Data collected was analysed using both descriptive and inferential statistics. The findings of the study reveal that children in Ekiti State, Nigeria love to engage in creative activities mostly in technical and vocational skills, and that they are motivated by their parents to do so. The study also found that even though the students do engage in creative activities in vocational activities, yet their vocational interest is much more on other disciplines order than vocational subjects as influenced by their parents. It is therefore recommended that parents and teachers should encourage children whenever they are engaged in creative activities at home and in schools and help those to develop their career based on the children’s areas of interest.